2019
DOI: 10.1093/toxsci/kfz210
|View full text |Cite
|
Sign up to set email alerts
|

Neuromelanin Modulates Heterocyclic Aromatic Amine-Induced Dopaminergic Neurotoxicity

Abstract: Heterocyclic aromatic amines (HAAs) are mutagens and potential human carcinogens. Our group and others have demonstrated that HAAs may also produce selective dopaminergic neurotoxicity, potentially relevant to Parkinson’s disease (PD). The goal of this study was to elucidate mechanisms of HAA-induced neurotoxicity through examining a translational biochemical weakness of common PD models. Neuromelanin is a pigmented byproduct of dopamine metabolism that has been debated as being both neurotoxic and neuroprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 101 publications
0
24
0
Order By: Relevance
“…[248,256,257] Studies from our lab have reported that PhIP generates reactive free radicals, leading to an increase in the accumulation of ROS. [43,258,259] Recently, our group showed that PhIP exposure for acute, subacute, and subchronic time points produced oxidative damage and alterations in synaptic proteins. Our study demonstrated that subchronic PhIP exposure promotes Aβ aggregation by increasing the levels of BACE1, APP, and oxidative damage.…”
Section: Dietary Toxinsmentioning
confidence: 99%
“…[248,256,257] Studies from our lab have reported that PhIP generates reactive free radicals, leading to an increase in the accumulation of ROS. [43,258,259] Recently, our group showed that PhIP exposure for acute, subacute, and subchronic time points produced oxidative damage and alterations in synaptic proteins. Our study demonstrated that subchronic PhIP exposure promotes Aβ aggregation by increasing the levels of BACE1, APP, and oxidative damage.…”
Section: Dietary Toxinsmentioning
confidence: 99%
“…The study of dietary neurotoxicants is important to a) determine the underlying pathogenic mechanisms that may influence neurodegeneration and b) identify modifiable risk factors that can limit the onset or progression of disease pathology. Previous studies have identified significant neurotoxic effects of dietary toxicants such as heterocyclic aromatic amines (HAA) on dopaminergic and cholinergic neurons, linking their potential association with AD and PD (5)(6)(7)(8)(9)(10). HAAs are produced in meat upon high temperature cooking, through Maillard reaction between amino acids, sugar, and creatinine or pyrolysis of aromatic amino acids (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is closely associated with the formation of kidney stones ( 31 ). Lawana et al ( 32 ) found that low doses of Harmane caused a 1.6-fold increase in reactive oxygen species (ROC) production in SH-SY5Y cells, which increased to 3.5-fold at higher doses. Furthermore, there was a dose-dependent increase in ROC synthesis in SH-SY5Y cells in response to Phlp and its metabolites.…”
Section: Discussionmentioning
confidence: 99%